F. novicida-Infected A. castellanii Does Not Enhance Bacterial Virulence in Mice - Ozanic, Mateja; Gobin, Ivana; Brezovec, Martin; Marecic, Valentina; Trobonjaca, Zlatko; Abu Kwaik, Yousef; Santic, Marina (Frontiers in Cellular and Infection Microbiology, 2016)
Francisella tularensis is a facultative intracellular bacterium that causes tularemia in humans and animals. Epidemiology of tularemia worldwide is often associated with water-borne transmission, which includes mosquitoes and amoebae as the potential host reservoirs of the bacteria in water environment. In vitro studies showed intracellular replication of F. tularensis within Acanthamoeba castellanii and Hartmanella vermiformis cells. While infection of amoeba by Legionella pneumophila has been shown to enhance infectivity of L. pneumophila the role of F. tularensis-infected protozoa in the pathogenesis of tularemia is not known. We used 6 h coculture of A. castellanii and F. novicida for investigation of the effect of inhaled amoeba on the pathogenesis of tularemia on in vivo model. Balb/c mice were infected intratracheally with F. novicida or with F. novicida-infected A. castellanii. Surprisingly, infection with F. novicida-infected A. castellanii did not lead to bronchopneumonia in Balb/c mice, and Francisella did not disseminate into the liver and spleen. Upon inhalation, F. novicida infects a variety of host cells, though neutrophils are the predominant cells early during infection in the lung infiltrates of pulmonary tularemia. The numbers of neutrophils in the lungs of Balb/c mice were significantly lower in the infection of mice with F. novicida-infected A. castellanii in comparison to group of mice infected only with F. novicida. These results demonstrate that following inoculation of mice with F. novicida-infected A. castellanii, mice did not develop tularemia.